Strategies to reduce occupational stress in health workers during the COVID-19 pandemic: a literature review (Research, Society and Development, 2020)
The pandemic caused by the disease COVID-19, considered a public health emergency in several countries, has had disastrous consequences for the health of the population. Among health professionals and services, this fact caused disorders in several aspects, including situations that promote occupational stress. Objective: To analyze strategies for reducing occupational stress in health workers during the COVID-19 pandemic. Methodology: The study was based on a qualitative literature review, from August to September 2020. National and international databases were used, including PubMED, Virtual Health Library (VHL) and Google Scholar. Results: It was possible to return 460 articles, and after analyzing and applying the eligibility criteria, 26 studies were able to follow the research. There was a diversity of potential factors that cause stressful situations, such as the fear of transmitting infection to the family, acquiring the disease and the fact that there is no specific treatment, as well as the existence of alternatives to protect the health of health professionals. Final considerations: Strategies were found such as training and preparation to deal with worrying situations similar to the experience of the COVID-19 pandemic, the creation of supportive environments and counseling services among health professionals, the imposition of community sanctions, the provision of tools digital media for meditation and relaxation, breathing work, mindfulness training and behavioral therapy are worth mentioning in this critical scenario.